Evaluation of Effectiveness of Different Treatment Regimens for Acute Bronchial Asthma in School-aged Children Depending on Type of Acetylation - S.I. Tarnavska (Zaslavsky O.Yu., 2012)
While carrying out check-up of 118 school-aged children with bronchial asthma, it was noted that severe form of asthma and accordingly more severe attacks were detected in patients with slow type of acetylation. Clinical features of the disease in children with slow type of acetylation determined significantly more frequent use of a short course of systemic glucocorticoids as compared with the fast acetylating phenotype. Indices of clinical and epidemiological risks were following: relative risk - 1.3 [95% CI 0.9-2.6], odds ratio - 3.7 [95% CI 1.3-6.7]. At the same time, in children with fast type of acetylation the usage of a complex anti-obstructive therapy with the inclusion of systemic corticosteroids, salbutamol, aminophylline compared to salbutamol monotherapy was more effective (reduction of attributable risk - 45.8 %, reduction of a relative risk - 82 % in minimum number of patients patients needed to treat to obtain a positive result - 2.2).